INTEGRASI KURIKULUM PAI DAN SAINS DI SEKOLAH DASAR - Ahmad Ardiansyah (AS-SALAM, 2014)
More recently, Indonesian education is facing many complex problems in which the root is the emergence of dichotomy between religious and science subjects. From that circumstance, it is strongly needed to have a fundamental concept to combine those two discrepant subjectsthrough?integration concept?.Curriculum integration is originally derived from ?integrated curriculum?.This terminology is a curriculum model that can integrate skills, themes, concepts, and topics, which lies under various frameworks:within single discipline, across several disciplines, and within and across learners.             Theoretically, the integration between religious and sciencesubjects is the concept that erasesdichotomy between these subjects. Despite from such advantegous sides, webbedmodel is, in fact, still considered to be the most suitable one used in learning process at elementary schoolsincethis model is designed as suited as possible with either theclassroom condition or the students. Besides, webbed model promotes phases to improve and foster values, which, consequently, needs many suggestions and acknowledgement from other partieswithin its learning process.             In terms of its actual application, webbed model is not separatedwith the principle of curriculum integration which combines certain aspects including skills, themes, concepts, and topics. As a result, through this research, there will be final products; comprise of syllabus and lesson plan integrated and/or in accordance withthe principle of curriculum integration.